Challenges in women’s healthcare: Management of molar pregnancy in a resource-limited rural Tanzanian hospital – a case report - Trojnarska, Dominika; Pietrzyk, Paulina; Mierzwa, Gabriela; Abraham, Ernest; Jach, Robert (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Providing healthcare in low- to lower-middle-income countries requires substantial effort from medical professionals. This case highlights the critical need for sustainable healthcare solutions to offer adequate care in such areas. The aim of this case report is to present the challenges faced by midwives, nurses, and doctors in Tanzania when providing standard care in resource-limited settings. A 30-year-old woman presented with vaginal bleeding and an enlarged uterus, diagnosed via transabdominal ultrasound as a molar pregnancy. Due to financial constraints, only essential tests and improvised surgical interventions, including a makeshift suction device, were performed. Despite these challenges, the procedure was successful, and the patient was discharged with follow-up recommendations. However, she did not attend the scheduled follow-up. This case underscores the difficulties in providing standard care in resource-limited settings and highlights the need for adaptive strategies, local healthcare training, and continued support for medical missions to improve healthcare in underserved regions.